Water Resource Management Strategies in the Citarum River Basin - Cahya, Darmawan Listya; Ummah, Andrian Khoirul (West Science Nature and Technology, 2025)
The Citarum River Basin is one of Indonesia’s most vital water sources, yet it faces severe degradation due to pollution, rapid industrialization, and unsustainable practices. This study explores water resource management strategies in the Citarum River Basin using a qualitative approach. Data were collected through in-depth interviews with three key informants: a government representative, a community leader, and an environmental activist. The findings reveal that effective water management requires integrated efforts involving regulatory enforcement, community participation, and environmental advocacy. While government programs such as the Citarum Harum Program provide a framework for restoration, weak law enforcement and limited stakeholder coordination hinder progress. Communities demonstrate willingness to participate but face resource and knowledge constraints, whereas civil society organizations play a vital role in advocacy and awareness-raising. The study concludes that sustainable management of the Citarum River demands multi-stakeholder collaboration, strong governance, and inclusive participation to balance ecological, social, and economic needs.